Home, neighborhood, and renewal: resident perceptions of forced relocation - Wilcox, F. Rowan (Kansas State University, 2009)
Given the ongoing incidence of housing displacement related to the commercial redevelopment of neighborhoods, and its implications for the health and quality of life of affected households and communities, there is a need for insight into what factors influence the quality of a move and movers' chances of successful post-move adjustment. In this study, qualitative analysis of in-depth interviews with 26 men and women representing 18 households from three redeveloped eastern Kansas neighborhoods was employed to examine residents' experiences of displacement. Five factors were examined: attachment to home and neighborhood, community social ties, relative sense of control and mastery over the circumstances of relocation, opinions of the amount of monetary compensation or relocation assistance received, and support for a redevelopment project. The results show that attachment to home influenced feelings about having to move, although it did not preclude contentment with a post-move dwelling. Attachment to neighborhood had both social and environmental components. Neighborhood social ties were difficult to replicate for many residents in their post-move neighborhoods. Perceptions of control over the circumstances of a move were negatively affected by problems with communication and information-sharing between residents and relocation authorities, causing stress and difficulties finding replacement housing. Satisfaction with compensation was tied to perceptions of upward housing mobility, while dissatisfaction was influenced by perceptions of having been a victim of official graft. Expressed support for redevelopment projects was in the main grudging, and support for a project did not appear to greatly influence a positive disposition toward moving. Experiences connected with displacement are not monolithic, and neither are its outcomes. Householders forced to move may concede that relocation has had at once negative repercussions and benefits. Having achieved upward housing mobility or experienced improved quality of life subsequent to moving did not eradicate residents' wish to have been 'treated better,' monetarily or otherwise, by relocation officials. This oft-expressed desire calls attention to the need for greater awareness of, and sensitivity to, the nature of residential place attachment and the special problems of those forced to move.
Keywords: Home; Neighborhood; Place attachment; Eminent domain; Housing displacement; Relocation; Geography (0366); Sociology, General (0626); Urban and Regional Planning (0999)